Analysis of the digital competences of the students of the degrees of the Faculty of Business, Finance and Tourism of the University of Extremadura - Arias Abelaira, Triana; Pache Durán, María; Mirón Sanguino, Ángel Sabino; Herrera Santos, Jorge (Revista General de Información y Documentación, 2024)
The demand for digital skills for life and work is growing every day. There is currently a Digital Education Action Plan (2021-2027), an initiative of the European Union (EU) to support the effective adaptation of education and training of all EU members in the digital age. The aim of this study is therefore to determine the level of digital competence of students at the Faculty of Business, Finance and Tourism of the University of Extremadura (Spain) and to identify whether or not there is a gender digital divide. To this end, a sample of 332 students from the aforementioned faculty was selected and, by applying the Digital Competences in Higher Education Questionnaire (CDES), the data collected were analysed using the SPSS software. The results of the study reflect a high level of digital competences (64.8%), 65.9% being male and 68.6% female, concluding, therefore, that there is no gender digital divide in our study universe.
Keywords: Digital skills; higher education; Business Administration and Management; gender digital divide